SITUATION AND PROSPECTS FOR DEVELOPMENT OF AGRICULTURE IN THE MUNICIPALITY OF BACKA TOPOLA - Дозет, Гордана; Цвијановић, Горица; Пузић, Горан (Economics of Agriculture, 2011)
Total area of municipality is 596 km2, of which 91.61% is agricultural land. In order to achieve economic growth municipalities, it is necessary to develop a strategy for development of the Municipality Backa Topola for a longer period, with special emphasis on analysis and opportunities for development of agriculture and its operationalization. Of pedological soil types prevalent chernozem. The land were broken, so that the average size of the possession of 4.27 hectares and the average size of 2.12 ha plot of land. Most arable land is arable cover crops, which is dominated by maize production at about 50% of the land. Yields of wheat, maize and sunflower in the last fve years analyzed above average in Serbia. SWOT analysis is performed, and received guidance on the facts and the intersection of state of agriculture in the municipality. It is necessary to intensify the primary agricultural production to the development of manufacturing. Activities are provided for the modernization of agriculture-specifc marketing development.